REGISTRASI KEPENDUDUKAN DALAM BIDANG PENCATATAN SIPIL BERDASARKAN UNDANG-UNDANG NO.23 TAHUN 2006 - Untung Sri Hardjanto, Indarja (Diponegoro Law Journal, 2012)
Resident registration is a way to count the number of residents with collecting data on the important events that happened in the community such as: birth, death, marriage, divorce, adoption, and others. Institute of Civil Registry is an institution established by the Government as the Implementing Agency for the record and record significant events that occur, to assure one's civil status. Exact status is evidenced by the issuing certificate. The Government established a policy regarding the administration of residence by Law. 23 of 2006 on Population Administration. In carrying out the registration in the field of civil government announced a population administration information systems (SIAK) make it easier to acquire and manage demographic data. Therefore, we need a study aimed at identifying potential problems arising from the provisions contained in the civil registry settings based SIAK and identify early problems in the registration process in the field of civil registration. As happened in the Kudus District are still many problems encountered in the field of civil registration.   Related to the above background, the authors conducted a study of the problems that arise concerning how SIAK arrangements in the field of civil registration, and how the registration process in the field of civil population and whether the constraints faced in the implementation and how the efforts to overcome them.   Seeing the issue, in legal writing, the writer uses the method juridical-normative and descriptive-analytical research specifications. then for the data collection method through literature study and interviews, while the qualitative data analysis is done.   Based on the research conducted, the result that setting SIAK in Kudus Regency set in Regulation 12 of 2008 on Population Administration Implementation adjusted to Law No.23 of 2006 on Population Administration. In carrying out the registration procedure, the Government Kudus undergone many obstacles. However, these barriers are overcome with such efforts and increase social approach ministry.   Keywords: Population Registration, under the Civil Registration Act No.23 of 2006 on Population reasonable legal